2010
DOI: 10.1002/ana.21972
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status is associated with relapse rate in pediatric‐onset multiple sclerosis

Abstract: Lower serum 25-hydroxyvitamin D(3) levels are associated with a substantially increased subsequent relapse rate in pediatric-onset multiple sclerosis or clinically isolated syndrome, providing rationale for a randomized controlled trial of vitamin D supplementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
242
1
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 316 publications
(257 citation statements)
references
References 33 publications
9
242
1
5
Order By: Relevance
“…Our study shows a clear relationship between vitamin D status and the relapse rate of RRMS patients, as previously reported in several association studies [Van der Mei et al 2007;Smolders et al 2008b;Mowry et al 2010;Simpson et al 2010], but our study is the first so far to observe this finding after systematic vitamin D supplementation. Furthermore, the global quantitative effect of the DSL increase on the relapse reduction found here (13.7% decrease in IR for every 10 nmol/l increase in DSL in the multivariate analysis) confirms the quantitative predictions made in two recent association studies [Mowry et al 2010;Simpson et al 2010], in which broadly similar figures were reported in RRMS patients, most of whom were not being supplemented with vitamin D. It should be noted that in one of these studies [Simpson et al 2010], most of the patients were also under first-line IMT, as in our cohort. However, the fundamental difference between our study and these previous studies is that almost all of our patients have to a greater or lesser extent eventually benefited from the vitamin D effect thanks to active, systematic supplementation.…”
Section: Relationship Between the Relapse Rate And Vitamin D Statussupporting
confidence: 91%
“…Our study shows a clear relationship between vitamin D status and the relapse rate of RRMS patients, as previously reported in several association studies [Van der Mei et al 2007;Smolders et al 2008b;Mowry et al 2010;Simpson et al 2010], but our study is the first so far to observe this finding after systematic vitamin D supplementation. Furthermore, the global quantitative effect of the DSL increase on the relapse reduction found here (13.7% decrease in IR for every 10 nmol/l increase in DSL in the multivariate analysis) confirms the quantitative predictions made in two recent association studies [Mowry et al 2010;Simpson et al 2010], in which broadly similar figures were reported in RRMS patients, most of whom were not being supplemented with vitamin D. It should be noted that in one of these studies [Simpson et al 2010], most of the patients were also under first-line IMT, as in our cohort. However, the fundamental difference between our study and these previous studies is that almost all of our patients have to a greater or lesser extent eventually benefited from the vitamin D effect thanks to active, systematic supplementation.…”
Section: Relationship Between the Relapse Rate And Vitamin D Statussupporting
confidence: 91%
“…Serum 25(OH) vitamin D (25OHD) levels were measured using chemiluminescence assay as previously described (Heartland Assays, Ames, IA) 26. 25OHD levels were used to adjust analyses because they are associated with risk of MS onset and MS outcomes, such as relapse and possibly disability 26, 27…”
Section: Methodsmentioning
confidence: 99%
“…25OHD levels were used to adjust analyses because they are associated with risk of MS onset and MS outcomes, such as relapse and possibly disability 26, 27…”
Section: Methodsmentioning
confidence: 99%
“…After MS onset, serum 25(OH)D 3 concentration declines [91] , and hypovitaminosis D is observed throughout the course of the disease, even in a clinically isolated syndrome (CIS) [92][93][94] . Thus, the studies measuring 25(OH)D 3 concentration in patients with MS are uninformative in deciding whether vitamin D can decrease the risk of MS [95,96] .…”
Section: Vitamin D and Msmentioning
confidence: 99%